Phenotyping Sjögren's syndrome: towards a personalised management of the disease - Brito Zeron, Pilar (2018)
Sjögren´s syndrome (SS) is a systemic autoimmune disease that mainly targets the exocrine glands. The disease overwhelmingly affects women around 30-60 years old, and more than 95% of patients present with oral and/or ocular dryness, although they may also develop a wide number of organ-specific systemic manifestations. The variable presentation is often linked to the influence of multiple personal determinants. In this review, we analyse the main geoepidemiological, immunological and histopathological determinants involved in the phenotypic expression of SS. With respect to sicca involvement, some patients (Asian, young-onset diagnosis, males and Ro-carriers) present with a less pronounced involvement in contrast to others with more pronounced dryness (seronegative, isolated La-carriers). With respect to the risk of developing systemic disease/poor outcomes, we propose a phenotypic-driven prognostic classification into patients at low risk (elderly-onset diagnosis, seronegative, isolated La-carriers), moderate risk (Black/African-american, young-onset diagnosis, Ro-carriers) and high risk (males, high focus score or presence of germinal centers in histopathological studies, RF-carriers, cryoglobulinaemic and hypocomplementaemic patients). Phenotype-based clustering of systemic autoimmune diseases may help physicians to offer a more personalised, cost-effective medical care of patients affected by these complex chronic diseases.